Reliability and acceptability of the multiple mini-interview for selection of residents in cardiology - Burgos, Lucrecia María (2020)
Introduction: The multiple mini-interview (MMI) model can be useful to evaluate non-cognitive domains and guide the selection process in medical residency programs. The aim of this study was to evaluate the reliability and acceptability of the MMI model for the selection of residents in a cardiology residency program. Methods: We conducted an observational and prospective study. It was performed in a tertiary-care center specialized in cardiology and included candidates for the cardiology residency program in March 2018. Ten stations were developed to evaluate different non-cognitive domains. Reliability was evaluated by the generalizability G coefficient. Candidates and interviewers were surveyed to evaluate the acceptability of the MMI model. Results: Nine faculty members were trained and 22 candidates were evaluated. The G study showed a relative G coefficient between 0.56 and 0.73, according to the design. 91% of the candidates stated that they preferred MMI over other types of interviews as a selection method for admission to the residency program, and all the interviewers considered they had enough time to evaluate the candidates and their strengths as future residents. Conclusion: The MMI is a reliable model to evaluate candidates for a residency program in cardiology with high acceptability among residents and observers.